Medical Sanitary Methods For Drying Fruits And Vegetables - Sulaymonova Zebiniso Ilyos qizi; Ranoqulova Sanobar Ikromovna; To'layev Bobur Zoyir o'g'li; Subxonova Zarnigor Sultonbek qizi (Euro Asian Journal Publishing, 2024)
Nowadays, a high level of growth is observed in the areas of growing agricultural products, processing, and producing import-substituting products. The production of canned and dried agricultural products is one of the leading branches of the food industry. When drying agricultural products, complex structures, energy- intensive techniques and technologies are used. Accordingly, it is important to create modern machinery and technologies using efficient, energy-saving, renewable energy sources necessary for the production of dried fruits and vegetables in the export sector
Keywords: Drying; radiation; raw; biochemistry